2020
DOI: 10.1155/2020/3409679
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Protective Mechanism of Crocin Pretreatment in Rat Submitted to Acute High-Altitude Hypoxia Exposure

Abstract: Inadequate oxygen availability at high altitude leads to oxidative stress, resulting in hippocampal neurodegeneration and memory impairment. In our previous study, we found that the cognitive dysfunction occurred when male SD rat was rapidly exposed to 4200 m of high altitude for 3 days. And we also found that crocin showed a cognitive protective effect under hypoxia by regulating SIRT1/PGC-1α pathways in rat’s hippocampus. In this article, focused on factors related to SIRT1/PGC-1α pathways, we proposed to fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 63 publications
(65 reference statements)
0
11
0
Order By: Relevance
“…SIRT1 expression was decreased in the hypobaric hypoxia‐induced cognitive model and crocin administration improved the SIRT1 and PGC‐1α levels. Therefore, the cognitive protective effect of crocin is related to SIRT1/PGC‐1 α pathway regulation (Zhang, Zhang, et al, 2018; Zhang, Zhang, et al, 2020). Furthermore, the antidepressant effect of crocin can be dependent on SIRT3 activation stimulation (Xiao et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…SIRT1 expression was decreased in the hypobaric hypoxia‐induced cognitive model and crocin administration improved the SIRT1 and PGC‐1α levels. Therefore, the cognitive protective effect of crocin is related to SIRT1/PGC‐1 α pathway regulation (Zhang, Zhang, et al, 2018; Zhang, Zhang, et al, 2020). Furthermore, the antidepressant effect of crocin can be dependent on SIRT3 activation stimulation (Xiao et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…According to report, SIRTI can activate transcription factors and metabolic coactivators, such as PGC-1α, by targeting selected genomic sites [45]. PGC-1α is a powerful transcriptional coregulator of mitochondrial genes, which can enhance the oxidative stress and mitochondrial respiration, and effectively improving the cognitive ability of rats [46]. Yang et al found that exogenous IGF-1 alleviated depression-like behavior and hippocampal mitochondrial dysfunction via promoting the expression of PGC-1α [47].…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, total RNA was isolated from the hippocampus of mice using TriZol reagent. 29 Total RNA was reverse transcribed into cDNA using a cDNA reverse transcription kit (TransScript All-in-one First-Strand cDNA Synthesis SuperMix for qPCR, Beijing Transgen Biotech Co., Ltd.) to amplify the cDNA. RT-PCR amplification was performed using QuantStudio1 (Thermo Fisher Applied Biosystems).…”
Section: H Hmentioning
confidence: 99%